ANALISIS KETERAMPILAN DASAR MENGAJAR MAHASISWA PENDIDIKAN TEKNIK BANGUNAN FT-UNP PADA SAAT PPLK DI SMK SE-KOTA PADANG - 451-459 , Arsyad Fachromi (Universitas Negeri Padang, 2014)
Abstract This research aims to analyze the basic skills to teach students technical education Buildings current UNP PPLK FT-in SMK Padang city of se-either in planning or carrying out the learning process. Preliminary observation on some schools that implement PPLK, there are some complaints by teachers ' teachers have indicated that there are students who do not prepare the planning and implementation of the learning process. This research is descriptive research to uncover how the mastery of basic skills to teach students at PPLK in SMK Padang city. The population is teachers ' teacher semester January-June 2014 as many as nine people. Instruments used include the now Likert scale models and descriptive analysis. Results of the analysis of data on indicators of ability to plan the learning process obtained the degree of achievement of the average 73,96% category is enough. On the learning ability of implementing indicators obtained then obtained an average of 71,02% category is enough. It was concluded that the basic skills to teach students technical education Building is included in the category of less skilled enough or. Key Words: Ability to plan, implement the learning process.